Computed Tomography Osteodensitometry for Assessment of Bone Mineral Density of the Canine Head—Preliminary Results - Glynn Woods; Nicolas Israeliantz Gunz; Ian Handel; Tiziana Liuti; Richard J. Mellanby; Tobias Schwarz (Animals, 2021)
Despite bone mineral density (BMD) being regularly measured in human patients, BMD studies in clinical cohorts of dogs is lacking. In order to facilitate BMD assessment and in turn better identify dogs suffering from metabolic bone disease, rapid, easy and precise computed tomography (qCT) techniques are required. In this study we aimed to assess the utility of quantitative computed tomography (qCT) bone mineral density (BMD) measurement of the canine calvarium using a semiautomated osteodensitometry software and define host factors associated with canine bone mineral density in a skeletally healthy population. Calvarial qCT at the level of the temporomandibular joints was performed on 323 dogs using a dedicated osteodensitometry calibration phantom during a clinically indicated head computed tomography (CT). Calvarial BMD was analyzed using a dedicated semiautomatic osteodensitometry software for contouring of the calvarial lamellar bone margins and BMD calculation. The mean duration of the calvarial qCT scanning was 64.6 s, and the mean duration of BMD analysis was 34 s, with a mean of two manual adjustments required for the bone margin tracing. The median BMD of all dogs in our study was 659 mg Calcium hydroxyapatite/mL. There was a negative linear correlation between BMD and body weight, but no correlation with age, sex or neutered status. Canine BMD assessment using qCT of the calvarium is a practical and fast technique that can be added to a clinical CT examination with minimal extra time requirements. Canine BMD host-dependent factors exhibit different relationships from that of humans; however, further investigation is warranted.